Leitura e teatro - Witter, Geraldina Porto (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2008)
Black, A.; Stave, A.M. A comprehensive guide to readers theatre: enhancing fluency and comprehension in middle school and beyond. Newark: IRA, 2007. xiv+233p. Acesso ao texto completo (PDF)